High levels of phenological asynchrony between specialized pollinators and plants with short flowering phases. Issue 11 (27th September 2020) - Maglianesi, María A.; Hanson, Paul; Brenes, Emanuel; Benadi, Gita; Schleuning, Matthias; Dalsgaard, Bo
Abstract: Species phenology plays a key role in determining mutualistic interactions, such as those between plants and pollinators. Notably, temporal synchrony shapes the patterns of interactions by influencing the probability of encounters between interacting partners; thus, species phenology greatly contributes to structuring ecological communities. In these communities, specialized species are expected to show a high level of synchrony with their partners; however, the relationship between species phenology and specialization remains largely unexplored. In three localities in the tropical mountains of Costa Rica, we quantified the level of phenological synchrony in plant–pollinator networks and tested whether phenological synchrony is associated with the degree of pollinator specialization on plant partners. We also tested the relationship between pollinator specialization and the length of the flowering phase of the visited plants. Across all three studied networks, our results show a strong asynchrony between interacting plant and pollinator species. We also found that more specialized pollinators were more asynchronous with their plant partners and, moreover, that specialized pollinators preferably visited plant species with shorter flowering phases compared to generalized pollinators. These patterns suggest that specialized pollinators may be more vulnerable to mutualistic disruptions because they depend primarily on short‐lived resources and have a high risk of phenological mismatch. This discovery has important consequences for specialized species' potential to survive and adapt to changes in the phenology of their interacting partners, which is highly relevant in a time characterized by changing climates and associated shifts in species phenology.